PEMANFAATAN TEKNOLOGI BAGI UMKM SELAMA PANDEMI COVID-19 - Mia Clarissa Dewi (iLearning Journal Center, 2020)
Technology is a necessity in this globalization, above all during Covid-19 pandemic. However, SMEs have a low level of digitization so that making it difficult to access technology in business. Therefore, it is necessary to identify technology utilization strategies that can be applied by SMEs for surviving during Covid-19 pandemic. Data were collected using observation method and analyzed descriptively. There are some strategies that can be implemented by SMEs include 1) the use of digital marketing which makes it easier for SMEs carrying out marketing activities and improve customers relationships; 2) using of e-commerce which supports SMEs for transactions; 3) the use of financial technology which help SMEs as electronic payments and financing or investing. Keywords: digital marekting, e-commerce, financial technology.